Factors affecting titratable acidity in raw milk - Karen A. Schmidt; J. Stupar; John E. Shirley; S. Adapa (Kansas Agricultural Experiment Station Research Reports, 1996)
The value of titratable acidity (TA) as an indicator of raw milk quality has been challenged recently, because milk is refrigerated within minutes after it leaves the cow until it reaches the consumer. Also, high milk protein may interfere with the test or confer falsely high TA values. Samples of milk containing 3.8% protein were used to examine the impact of protein on TA. The effects of milk age and bacterial counts also were investigated. Titratable acidity increased as milk protein content increased but the influence of bacterial populations and age were much more dramatic. As bacterial counts increased, TA values surpassed an acceptable level (upper maximum at .17%) for the KSU Dairy Processing Plant. At the same time, as raw milk increased in age, TA increased to the upper level of acceptability (.17%). Thus, TA appears to be a valid method of evaluating raw milk quality even though it can be influenced by the protein content.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Titratable acidity; Raw milk; Quality